PENGUJIAN KUAT TEKAN BETON KARAKTERISTIK MENGGUNAKAN SEMEN OPC TYPE I, PPC DAN PCC - Samsuardi - Batubara; Wanapri Pangaribuan (Universitas Negeri Medan, 2023)
Cement is the primary material in the manufacture of concrete. In Indonesia, several types of cement are available, namely OPC, PCC, and PPC cement. OPC cement is the predominantly most common and used, whereas PCC and PPC cement were introduced later. The application of OPC cement is more commonly used, and recommended by planners in work plans and specifications document. Based on this, a comparative study of the characteristic compressive strength of concrete was carried out using OPC Type 1 cement, PCC, and PPC cement. This research aims to determine the possibility of using PCC (Portland Composite Cement) and PPC (Portland Pozollan Cement) in construction work. The research was carried out experimentally by making test specimens in the laboratory using OPC, PPC, and PCC cement for 2 (two) designed characteristic compressive strength f'c=20.75 MPa and f'c=24.90 MPa. The Job mix design for the two f'c strength design was based on SNI 7656:2012. The result shows that the characteristic compressive strength of concrete using Andalas cement (OPC) increased by 122% and 125%, and PCC cement from Padang cement increased by 107% and 118%. Meanwhile, the Bima cement type (PPC) did not reach the designed compressive strength, as it reached only 89% of the design compressive strength.Keywords : Concrete, Cemen, OPC, PPC, PCC